INTERNATIONAL COOPERATION: THE MAIN DIRECTIONS OF IMPLEMENTATION - М. М. Abazalieva; A. К. Botasheva (Современная наука и инновации, 2023)
The fundamental issue of modern international relations is the preservation of the national state as the main world political actor. Consequently, the relations of states (the format of these relations, legal foundations, tools and directions of implementation) remain a factor on which the development and functioning of the entire world political system largely depends. In such circumstances, it is of paramount importance to study the forms and directions of interaction between states as the main actors of world politics. It is concluded that the main and most constructive direction of such interaction was and is international cooperation, the main and ultimate goal of which is to create favorable conditions for the realization of their own national interests.